Habitus Primer pada Anak Berkonflik dengan Hukum - Diana Dewi Sartika; Safira Soraida; Gita Isyanawulan; Yosi Arianti (Society, 2022)
Children are assumed to be innocent entities and have not much experience. However, the emergence of the phenomenon of children as perpetrators of crimes (children in conflict with the law/CICL) is contradictory to this assumption. This study explores and examines one aspect of the life of the child perpetrator of this crime, namely the family aspect as the primary habitus. This study used qualitative research methods by interviewing CICL at the Palembang Special Children’s Correctional Institution and Correctional Institution of Kayuagung, Ogan Komering Ilir Regency, as well as several related figures. Data were collected by observation, in-depth interviews, and documentation. Meanwhile, data analysis is built from the ground up, linearly and hierarchically. In line with the focus of the study, the concept used in this study is the primary habitus, which is part of the habitus concept of Bourdieu. The primary habitus is the habitus that the agent has since childhood, which is the basis for forming other (secondary) habitus. The research results related to primary habitus in CICL show that the family is not present as a whole in the process of CICL growth and development and the application of ineffective parenting. Complete absence of the family, shown to the family by the presence of, 1). CICL with separated parents, 2). CICL with one or both parents died, 3). CICL has an intact family but is not fully present in the child’s growth and development process. Meanwhile, poor parenting is shown through 1). Parenting with violence, 2). CICL’s parents and close people have not become positive role models, and 3). Parents do not/less comprehensively provide knowledge and understanding regarding good and bad deeds. Therefore, it is necessary to strengthen the family institution as a primary institution and an institution of value inheritance through socialization and education between generations. The family can be the main basis for passing down the values ??of anti-violence and crime in supporting efforts to minimize crime habitus.